A qualitative systematic review of service user and service provider perspectives on the acceptability, relative benefits, and potential harms of art therapy for people with non‐psychotic mental health disorders. (3rd June 2016) - Scope, Alison; Uttley, Lesley; Sutton, Anthea
Abstract : Purpose: This systematic review aimed to synthesize qualitative evidence relating to user and service provider perspective on the acceptability and relative benefits and potential harms of art therapy for people with non‐psychotic mental disorders. Methods: A comprehensive literature search was conducted in 13 major bibliographic databases from May to July 2013. A qualitative evidence synthesis was conducted using thematic framework synthesis. Results: The searches identified 10, 270 citations from which 12 studies were included. Ten studies included data from 183 service users, and two studies included data from 16 service providers. The evidence demonstrated that art therapy was an acceptable treatment. The benefits associated with art therapy included the following: the development of relationships with the therapist and other group members; understanding the self/own illness/the future; gaining perspective; distraction; personal achievement; expression; relaxation; and empowerment. Small numbers of patients reported varying reasons for not wanting to take part, and some highlighted potentially negative effects of art therapy which included the evoking of feelings which could not be resolved. Conclusions: The findings suggest that for the majority of respondents art therapy was an acceptable intervention, although this was not the case for all respondents. Therefore, attention should be focussed on both identifying those who are most likely to benefit from art therapy and ensuring any potential harms are minimized. The findings provide evidence to commissioners and providers of mental health services about the value of future art therapy services. Practitioner points: Art therapy was reported to be an acceptable treatment for the majority of respondents. Art therapy may not be a preferred treatment option for a small number of patients, emphasizing the importance of considering patient preference in choice of treatment, and selection of the most suitable patients for art therapy. Consideration should be made of adjustments to make art therapy inclusive, particularly for those with physical illnesses. Ensuring the competence of the deliverer, providing patients with additional support, such as other therapies if required, and ensuring continuity of care should be key considerations in service provision.